University course advising: overcoming the challenges using decision support system - Roushan, Tanvir; Chaki, Dipankar; Hasdak, Onishim; Chowdhury, Md. Syeed; Rasel, Annajiat Alim; Rahman, M. Abdur; Arif, Hossain (© 2014 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 16th International Conference on Computer and Information Technology, ICCIT 2013; Khulna; Bangladesh; 8 March 2014 through 10 March 2014; [© 2014 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICCITechn.2014.6997355